Enhancement in sensitivity of graphene-based zinc oxide assisted bimetallic surface plasmon resonance (Spr) biosensor - Kumar R.; Kushwaha A.S.; Srivastava M.; Mishra H.; Srivastava S.K. (My University, 2025)
In the present communication, a highly sensitive surface plasmon resonance (SPR) biosensor with Kretschmann configuration having alternate layers, prism/zinc oxide/silver/gold/graphene/biomolecules (ss-DNA) is presented. The optimization of the proposed configuration has been accomplished by keeping the constant thickness of zinc oxide (32 nm), silver (32 nm), graphene (0.34 nm) layer and biomolecules (100 nm) for different values of gold layer thickness (1, 3 and 5 nm). The sensitivity of the proposed SPR biosensor has been demonstrated for a number of design parameters such as gold layer thickness, number of graphene layer, refractive index of biomolecules and the thickness of biomolecules layer. SPR biosensor with optimized geometry has greater sensitivity (66 deg/RIU) than the conventional (52 deg/RIU) as well as other graphene-based (53.2 deg/RIU) SPR biosensor. The effect of zinc oxide layer thickness on the sensitivity of SPR biosensor has also been analysed. From the analysis, it is found that the sensitivity increases significantly by increasing the thickness of zinc oxide layer. It means zinc oxide intermediate layer plays an important role to improve the sensitivity of the biosensor. The sensitivity of SPR biosensor also increases by increasing the number of graphene layer (upto nine layer). © Springer-Verlag GmbH Germany, part of Springer Nature 2018.